2018
DOI: 10.3390/su10114039
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Ad-Blocking on the Sustainable Development of the Digital Advertising Ecosystem

Abstract: Despite the rapidly growing expenditure on digital advertising, the effectiveness of the functioning of the digital advertising ecosystem is becoming less and less visible. This is related to the fact that only a small part of the expenditure incurred by organizations on various forms of digital advertising brings the expected results. For several years now, a phenomenon that stifles the effectiveness of the digital advertising ecosystem and deteriorates the ROI (return on investment) of advertisers has been t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 7 publications
1
16
0
Order By: Relevance
“…First of all, the aim was to ensure that the persons participating in the research belong to the circle of persons who use the Internet, and use social media intensively. The literature analysis and previous studies clearly show that students are definitely such persons [6]. Secondly, it was important for the survey to include persons from the so-called Generation Z; namely, people born in the mid-1990s and later.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…First of all, the aim was to ensure that the persons participating in the research belong to the circle of persons who use the Internet, and use social media intensively. The literature analysis and previous studies clearly show that students are definitely such persons [6]. Secondly, it was important for the survey to include persons from the so-called Generation Z; namely, people born in the mid-1990s and later.…”
Section: Methodsmentioning
confidence: 99%
“…The hypotheses were formulated based on the completed literature analysis (see sections 1-3), also taking into account the results of the author's previously published studies (see [6]). It relates In total, the survey covered a group of 612 respondents (about 100 people from each of the faculties covered by the study), and assumed questionnaires completed directly with the use of Google Forms (the total number of full-time students at the Opole University of Technology is 3059).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The PageFair report's index of blocking ads for Poland in 2017 [1] amounted to 33%, while in 2015 it maintained the level of 34.9%. Another study published in 2018 showed that 61.2% of Polish internet users are using ad blocking software [41]. Apparently, the reason for this phenomenon is the overload with advertisements.…”
Section: Reasons For Usage Of Adblock Softwarementioning
confidence: 99%